2008
DOI: 10.1098/rspb.2008.0594
|View full text |Cite
|
Sign up to set email alerts
|

Fungal endosymbionts of plants reduce lifespan of an aphid secondary parasitoid and influence host selection

Abstract: Complex biotic interactions shape ecological communities of plants, herbivores and their natural enemies. In studies of multi-trophic interactions, the presence of small, invisible micro-organisms associated with plants and those of a fourth above-ground trophic level have often been neglected. Incorporating these neglected factors improves our understanding of the processes within a multi-trophic network. Here, we ask whether the presence of a fungal endosymbiont, which alters plant quality by producing herbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 38 publications
3
21
1
Order By: Relevance
“…Our results are in agreement with previous studies on parasitoids where mainly negative effects were recorded (Barker and Addison 1996;Bultman et al 1997Bultman et al , 2003de Sassi et al 2006). Similar detrimental effects of endophytes on the reproductive ability of the aphid parasitoid A. ervi and coccinellid predator have been demonstrated (Harri et al 2008;de Sassi et al 2006). This reduction in reproductive success could have been due to parasitoid exposure during larval development to the fungal toxin present in the host insect that weakened the parasitoid females, which laid fewer eggs with reduced viability.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results are in agreement with previous studies on parasitoids where mainly negative effects were recorded (Barker and Addison 1996;Bultman et al 1997Bultman et al , 2003de Sassi et al 2006). Similar detrimental effects of endophytes on the reproductive ability of the aphid parasitoid A. ervi and coccinellid predator have been demonstrated (Harri et al 2008;de Sassi et al 2006). This reduction in reproductive success could have been due to parasitoid exposure during larval development to the fungal toxin present in the host insect that weakened the parasitoid females, which laid fewer eggs with reduced viability.…”
Section: Discussionsupporting
confidence: 94%
“…The adverse effects of E+ plants on the longevity of female wasps subsequently resulted in reduced fecundity and egg hatchability. Our results are in agreement with previous studies on aphids where negative effects were found on endophyte-naive Aphidius ervi (Haliday) females (Harri et al 2008). Although E+ plants did not influence the parasitism rate of female wasps, they negatively affected their longevity and fecundity.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In accordance with previous experimental results for other host grass species (reviewed by Clay 1996; Cheplick and Faeth 2009), we found that endophyte presence strongly reduced the density of aphids attacking the native grass Poa autumnalis. Endophyte-symbiotic plants had both lower densities of live aphids and lower densities of parasitized aphids, indicating a bottom-up, community-level response to endophyte symbiosis, consistent with previous work (Faeth and Bultman 2002;Finkes et al 2006;Härri et al 2008a;Rudgers and Clay 2008). For example, in a similar study on the introduced grass species, Lolium multiflorum, Omacini et al (2001) found a decline in secondary parasitism that led to a less complex arthropod community structure in the presence of an endophyte.…”
Section: Discussionsupporting
confidence: 80%